Model Sistem Pendukung Keputusan Menentukan Tempat Pembuangan Akhir Sampah di Kotamadya Pangkalpinang - Hilyah Magdalena; Hadi Santoso; Henny Rahayuningsih; Karina Rochmayani; Oktoranda oktoranda (Fakultas Ilmu Komputer, Universitas Klabat, 2019)
Handling the problem of waste in the city of Pangkapinang as the Capital of the Province of Bangka Belitung is currently experiencing obstacles difficult to find landfill that is suitable for needs. Landfill landfill must meet several criteria related to tools, land, government administration, residents, and infrastructure. In addition to multi criteria, choosing a landfill also has multiple alternatives, namely the expansion of Trench Six as the initial landfill, and several villages located on the border of Pangkalpinang City, Namang Village, Big Puding Village, Jelutung Village, and Air Kuning Village. Based on the conditions for selecting multi-criteria and multi-alternative landfill landfill, this study was designed to analyze the decision support factors for selecting waste disposal sites for the City of Pangkalpinang using the AHP Analytical Hierarchy Process method. AHP was chosen as a research method because it was able to produce decisions by comparing pairing values between criteria and between alternatives. The results of data processing with AHP show that the highest criteria for land percentages weigh 33.5% and the chosen alternative is Namang Village with a weight of 34.3%.